Analisis Atas Prosedur Pembiayaan Kredit Pemilikan Rumah BTN Platinum: Studi Kasus pada PT. Bank Tabungan Negara (Persero) Tbk Kantor Cabang Bogor - Sa'diah, Firda Astrid; Syarif, Rini; Azhar, Zul (Jurnal Aplikasi Bisnis Kesatuan, 2024)
To facilitate its role as a fund distributor to the public, the bank has established credit financing procedures. With these procedures, the bank can process credit financing in a uniform, systematic manner, in accordance with government regulations and the bank's own policies. Credit financing procedures also help the bank assess the feasibility of potential debtors and reduce the risks associated with credit financing. This paper aims to understand the procedures for Home Ownership Loans (Kredit Pemilikan Rumah, KPR) at PT. Bank Tabungan Negara (Persero) Tbk and to determine the alignment of these procedures with general credit financing procedures. This research was conducted at the Bogor Branch Office of PT. Bank Tabungan Negara (Persero) Tbk. The results show that the Home Ownership Loan (KPR) procedures at PT. Bank Tabungan Negara (Persero) Tbk comply with the general Home Ownership Loan (KPR) financing procedures, although there are minor differences due to the specific regulations of PT. Bank Tabungan Negara (Persero) Tbk. The requirements and conditions set by PT. Bank Tabungan Negara (Persero) Tbk are still relatively light and easy to fulfill. However, there are some challenges in the financing procedures, such as system errors and data discrepancies between the information provided by potential debtors and the data available at the civil registry office (disdukcapil).   Keywords: Procedures, Credit, Home Ownership Loans